Neuroprotection - Chuen-Chung Chang, Raymond; Ho, Yuen-Shan (IntechOpen, 2019)
Neuroprotection is a strategy to prevent or delay the progression of chronic neurodegenerative diseases, acute neurological disorders, or even mental disorders. The major aim of this book is to focus on different approaches to achieve neuroprotection. In this book, there are chapters discussing imidazoline ligands and opioid ligands in Alzheimer's disease, the beneficial effects of adenosine A2A receptor antagonist, adrenergic receptor agonists and antagonists modulating microglial responses, and different approaches to achieve neuroprotection against aging-associated macular degeneration. This book will give insights to scientists in the field to stimulate their research, medical professionals to review their clinical practices, and others who would like to learn more about different neuroprotective approaches.